DEVELOPMENT MODEL OF BUILT OPERATE AND TRANSFER (BOT) OVER WAQF LAND PRODUCTIVITY - Monaya, Nova (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2017)
Build, Operate, Transfer (BOT) is an agreement that provides solutions between parties that have common interests but with their respective limitations that require the ability or ability of others to realize mutual benefits, for example one party has a plot of land that can be optimized for the benefit of the business to take advantage of the assets owned but due to limited funds or expertise in the field of asset management owned by inviting third parties to optimize the land to be utilized. From the BOT agreement there are many things that can be done and many advantages from third party communities including landowners, so that the land is not abandoned land or sleeping land. Waqf in the context of positive law as Law No. 41 of 2004 on Waqf, has inherited the rigid, closed, and narrow nature of its movement space permanently. This is due to the excessive concerns of the Naqwa waqf and the people around the land of waqf. Due to the nature of this rigidity, many land waqf which became the land of sleep, especially the manager of education and social activities, whereas land waqf land in a strategic location. This study aims to find a way out of the legal deadlock by harmonizing the law of land waqf with the approach of the law of covenant and the law of civil and land law as a pillar of increasing land productivity waqf. The research method used is a normative juridical approach with secondary legal materials from experts as well as comparative studies abroad that have implemented BOT on waqf land or utilizing objects on land waqf in perspective Islamic Business Law.Keywords : Built Operate Transfer (BOT), Waqf Law, Horizontal Separation Principle